Flowthrough of 239PU and 55FE during RNA extraction. (1st March 2023) - Manglass, Lisa M; Vogel, Charlotte M; Wintenberg, Molly; Blenner, Mark A; Martinez, Nicole E
Abstract: Analysis of gene expression has become an important tool in understanding low-dose effect mechanisms of ionizing radiation at the cellular level. Metal binding to nucleic acids needs to be considered when interpreting these results, as some radioactive metals, particularly actinides, may produce free radicals and cause oxidative stress damage via chemical means at rates much higher than free radical formation related to their radiological properties. Bacteria exposed in situ to low dose rates of plutonium-239 ( 239 Pu) and iron-55 ( 55 Fe) were previously analysed for gene expression. The work herein was motivated by an interest in more precisely identifying the distribution of radionuclides in these bacteria as well as the practical need to ensure appropriate transport and handling of the associated ribonucleic acid (RNA) extractions. RNA extractions were performed on bacteria growth media with and without bacteria cells (i.e. with and without RNA) at several different concentrations of 239 Pu and 55 Fe to inform the level of specificity of the extraction membrane as well as provide insight into internal (uptake) vs external (sorption) accumulation of these radionuclides in bacteria cells. Results of the study suggest that 239 Pu and 55 Fe detected in RNA extraction samples during long term cell studies is the result of binding to RNA prior to the time of extraction, as opposed to flow through or binding after cell lysis, and it highlights the practical importance of nucleic acid sample characterization to radiation protection more generally.